2009
DOI: 10.1016/j.stem.2009.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody-Mediated Targeting of CD123, IL-3 Receptor α Chain, Eliminates Human Acute Myeloid Leukemic Stem Cells

Abstract: Leukemia stem cells (LSCs) initiate and sustain the acute myeloid leukemia (AML) clonal hierarchy and possess biological properties rendering them resistant to conventional chemotherapy. The poor survival of AML patients raises expectations that LSC-targeted therapies might achieve durable remissions. We report that an anti-interleukin-3 (IL-3) receptor alpha chain (CD123)-neutralizing antibody (7G3) targeted AML-LSCs, impairing homing to bone marrow (BM) and activating innate immunity of nonobese diabetic/sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
386
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(412 citation statements)
references
References 53 publications
12
386
1
3
Order By: Relevance
“…This discovery was followed by several efforts aimed at targeting the hematopoietic cancer stem cell markers, such as CD44 and CD123 in AML [64][65][66][67][68]. Further studies have since been performed by targeting CSCs in several solid tumors such as pancreatic, breast, prostate and colon cancers, melanoma, glioma, hepatocellular carcinoma, and others.…”
Section: Targeted Therapy-targeting Cscs In Wtmentioning
confidence: 99%
“…This discovery was followed by several efforts aimed at targeting the hematopoietic cancer stem cell markers, such as CD44 and CD123 in AML [64][65][66][67][68]. Further studies have since been performed by targeting CSCs in several solid tumors such as pancreatic, breast, prostate and colon cancers, melanoma, glioma, hepatocellular carcinoma, and others.…”
Section: Targeted Therapy-targeting Cscs In Wtmentioning
confidence: 99%
“…A recent report demonstrates that treatment of AML mononuclear cells with anti-CD38 antibodies prior to transplantation inhibits engraftment in NS mice, suggesting that CD38 + subsets may contain LSCs (21). Also, several groups have shown that treatment of mice with anti-CD44, anti-CD47, or anti-CD123 can inhibit growth of LSCs or their engraftment in NS mice (22)(23)(24). It is not clear whether these antibodies interfere with BM homing or stimulation of intracellular signaling or through Fc-mediated clearance of antibody-labeled cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…Also, several groups have shown that treatment of mice with anti-CD44, anti-CD47, or anti-CD123 can inhibit growth of LSCs or their engraftment in NS mice (22)(23)(24). It is not clear whether these antibodies interfere with BM homing or stimulation of intracellular signaling or through Fc-mediated clearance of antibody-labeled cells (22). Furthermore, Taussig et al have observed that both CD34 -and CD34 + fractions from the majority of primary NPM1-mutated AML contained LSCs (25).…”
Section: Introductionmentioning
confidence: 99%
“…A number of therapeutic agents with similar molecular formats as those described for CD33 have been developed, including immunoglobulins, 47–49 a radio-immunoconjugate, 50 ADCs and a fusion protein between the cytokine IL-3 and a fragment of diphtheria toxin, 51–54 bi-specific T cell-recruiting agents (BiTEs) and Dual-Antigen Recruiting T-cell engagers (DARTs), 55–58 dual-targeting triplebodies, 59,60 and CAR-transfected T cells. 61–64 Expression of CD123 is largely restricted to hematopoietic cells, but expression on endothelial cells has been reported.…”
Section: Introductionmentioning
confidence: 99%